Guatemalan and Nicaraguan children and the test of playfulness - Phillips, Heather Ann, author; Bundy, Anita C., advisor; Pressel, Esther, committee member (Colorado State University. Libraries, 1998)
As play is influenced by culture, culture is influenced by play. Hence, it is important for professionals who work with children from different cultural backgrounds to evaluate play in their young clients. Objective evaluation demands reliable and valid instruments. The purpose of this study was to (a) determine whether the Test of Playfulness (ToP) demonstrates preliminary interrater reliability for Spanish speaking children in Guatemala and Nicaragua; and (b) examine if the ToP demonstrates preliminary construct validity? Specifically, will data from all raters conform to the expectations of the Rasch model even though the raters represent a different socioethnic background? And, will data from at least 95% of the children reflect goodness of fit to the Rasch measurement model? In addition, characteristics of childrearing in Hispanic families, the relationship between play and culture, and the influence of resilience in "at-risk" children are reviewed. Fifteen Guatemalan children with no known disabilities and 15 Nicaraguan children with and without known disabilities participated in this study (16 girls, 14 boys; age range 14 months to 17 years). Goodness of fit statistics generated with Rasch analysis revealed that data from 100% of raters and 97% of participants conformed to the expectations of the Rasch measurement model. Thus, we concluded that the ToP is valid and reliable; that is, the ToP reflects a construct of playfulness that is cross-cultural and it can be given reliably by raters from different socioethnic backgrounds. In addition, the findings revealed several things about Guatemalan and Nicaraguan children's play. (a) The high scores received by many of the children on the ToP suggested these are very playful children (12 of 30 received scores over 1.0). And (b) unexpected ratings on some items may reflect minor cultural variations in playfulness or the effect of raters from different socioethnic backgrounds. Implications and the need for further research are discussed.
Keywords: Play assessment (Child psychology); Play -- Cross-cultural studies